Structural characterization and in vitro hypoglycaemic activity of glucomannan from Anemarrhena asphodeloides Bunge. Issue 4 (27th January 2022) - Chen, Juncheng; Wan, Liting; Zheng, Qingsong; Lan, Meijuan; Zhang, Xia; Li, Yuting; Li, Bing; Li, Lin
Abstract : A new polysaccharide (AABP-2B) was obtained from Anemarrhena asphodeloides Bunge after purification by gradient alcohol precipitation and DEAE-52 cellulose column chromatography. Abstract : A new polysaccharide (AABP-2B) was obtained from Anemarrhena asphodeloides Bunge after purification by gradient alcohol precipitation and DEAE-52 cellulose column chromatography. AABP-2B was confirmed to be a homogeneous polysaccharide with a molecular weight of 5800 Da and was composed of mannose and glucose at a molar ratio of 7.2 : 2.8. Structural analysis demonstrated that the backbone of AABP-2B was mainly composed of 4)-β-d -Man p -(1, 4, 6)-β-d -Glc p -(1 and 3, 6)-β-d -Man p -(1. The hypoglycaemic effect of AABP-2B was evaluated by its inhibition of α-glucosidase activities and insulin resistance in a HepG2 cell model. The results showed that AABP-2B displayed α-glucosidase inhibitory activities and could significantly improve glucose consumption by activating the IRS-1/PI3K/Akt signalling pathway in insulin-resistant HepG2 cells. Hence, AABP-2B may have potential as a functional food or medicine for diabetes therapy.